Hubungan kadar natrium dengan tekanan darah pada remaja di Kecamatan Bolangitang Barat Kabupaten Bolaang Mongondow Utara - Polii, Rivanli; Engka, Joice N.A.; Sapulete, Ivonny M. (eBiomedik, 2016)
Abstract: Sodium is an extracellular fluid cation which is the highest in amount, 35-40% sodium (Na) is found in the body skeleton. The function of sodium is the regulation of fluid volume, the regulation of fluid balance, the regulation of osmolarity, and the regulation of blood pressure. Blood pressure is the force that is needed to keep the blood flowing inside the blood vessel and circulates to reach all the tissues in human body. Blood pressure consists of two components, the systolic pressure and diastolic pressure. According to the study conducted by Riset Kesehatan Dasar on 2007, it was found that the Natuna Islands (coastal areas) has the highest prevalence of hypertension, which is 53,3%, while the highlands of Jayawijaya has the lowest prevalence of hypertension, which is 6,8%. The North Bolaang Mongondow regency, especially West Bolangitang district is an area which is conditioned around the coastal areas. Adolescents, according to WHO, are those aged 12-24 years old. This was an analytical descriptive research is conducted with a cross sectional study design. Afterward, the collected datas are processed using the help of SPSS software. The population is all of the students in SMAN 1 Bolangitang Barat, North Bolaang Mongondow regency and the samples were collected with purposive sampling technique. The results showed that the number of respondents who follow the research were 60 students, consisting 16 boy and 44 girl by spearmanâ€™s correlation statistical test.This study shows no correlation between the levels of sodium and blood pressure on adolescents in West Bolangitang district North Bolaang Mongondow regency. Conclusion: there is no correlation between the levels of sodium and blood pressure on adolescents in West Bolangitang district, North Bolaang Mongondow regency. Keywords: sodium, blood pressure, adolescentÂ Abstrak: Natrium ialah kation terbanyak dalam cairan ekstrasel , 35-40% natrium (Na) ada didalam kerangka tubuh. Fungsi natrium untuk mengatur volume cairan, mengatur keseimbangan cairan, mengatur osmolaritas, dan mengatur tekanan darah. Tekanan darah adalah kekuatan yang diperlukan agar darah dapat mengalir di dalam pembuluh darah dan beredar mencapai semua jaringan tubuh manusia. Tekanan darah terdiri atas 2 bagian tekanan sistolik dan tekanan diastolik. Berdasarkan data yang dilakukan Riset Kesehatan Dasar tahun 2007 didapatakan bahwa prevalensi hipertensi tertinggi di Kepulauan Natuna (wilayah pantai) sebanyak 53,3 % sedangkan prevalensi hipertensi terendah di pegunungan jayawijaya sebanyak 6,8%. Kabupaten Bolaang mongondow utara khususnya Kecamatan Bolangitang Barat merupakan suatu wilayah yang terletak disekitaran pesisir pantai, Remaja menurut WHO adalah mereka yang berumur 12-24 tahun. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Data diolah dengan menggunakan program SPSS. Populasi ialah semua siswa/i SMAN 1 Bolangitang Barat Kabupaten Bolaang Mongondow Utara dan sampel diambil dengan cara purposive sampling. Hasil uji korelasi Spearman menunjukkan tidak terdapat hubungan antara kadar natrium dengan tekanan darah pada remaja di Kecamatan Bolangitang Barat Kabupaten Bolaang Mongondow Utara. Simpulan: Tidak terdapat hubungan antara kadar natrium dengan tekanan darah pada remaja di Kecamatan Bolangitang Barat Kabupaten Bolaang Mongondow Utara.Kata kunci: natrium, tekanan darah, remaja